STRATEGY OF HUMAN CAPITAL DEVELOPMENT AS ONE OF THE PRIORITIES DIRECTION OF MODERN GOVERNANCE - P. Galkin; I. Svetlov (Вестник университета)
The article outlines the specifics of the formation of new modern requirements for human capital, which is regarded as one of the central factors of the long-term development of the national economy. The need to develop a strategy for the development of national human capital, taking into account the specifics of functioning of economic systems, the latest technological structures, market demands and trends in the transformation of the world economic system is shown. Reviewed data reports allow to identify key areas for government attention in the context of strategic development of national human capital, thereby ensuring long-term foundation for the competitiveness of national economy of the Russian Federation.